Analisis Channel Youtube Sebagai Wakaf Produktif - Ahmad Nur Ahsan; Didin Hafidhuddin; Qurroh Ayuniyyah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Waqf is one solution in the development of Islamic progress. The benefits of waqf are not only felt by the recipient of the waqf, but it is also beneficial for the giver of the waqf as a reward that continues to flow. The management of waqf into productive waqf is more beneficial to the community, because the results of productive waqf will return to the community. The more productive waqf owned by Muslims, the better. The results of productive waqf can be used to support the progress of Muslims from various aspects. Productive waqf in the digital era as it is today has many kinds, including waqf with a youtube channel. Building a YouTube channel certainly requires creativity, time, energy and thought. Someone who builds a youtube channel must pay attention to the content created. Content must be in accordance with Islamic Shari'ah, there are no videos or video clips containing things that are prohibited by Shari'ah. Until now, there have been no Muslims who have been moved to donate a Youtube channel, considering that the Youtube channel that has been built is a source of income and still has the potential nowdays and there are no special waqf regulations that regulate waqf using the Youtube channel. This study uses a qualitative method with a normative conceptual approach, namely the approach taken for a problem for which there is no legal regulation. Primary and secondary data sources are collected and studied to produce legal analysis that is in accordance with the problem being studied. The primary sources in this study are the Qur'an, hadith, state laws, guidelines for waqf management and Youtube Community Guidelines, while secondary sources are classic books, books, articles, journals and documents related to the discussion. Youtube channels that are donated must be clean from violations of Youtube community rules so that they are easy to monetize. After that, the process of submitting to Nadzir is the same as handing over waqf of Intellectual Property Rights, because the Youtube channel is a type of intellectual property. The management of the Youtube channel by Nadzir must be in accordance with the Shari'ah. Uploaded content is prohibited from leading to immorality or a stimulus to commit immorality. Content must also comply with state laws, such as having to pay attention to copyright policies. Every work has a copyright that is protected by law, if the channel contains content with someone else's copyright, it must be with the permission of the copyright owner. Likewise, the advertisements displayed on the waqf youtube channel must be in accordance with the Shari'ah. The management of waqf Youtube channels must also comply with state waqf rules. The authorized waqf supervisor must know the monthly income, operational costs for creating content and the net profit received for waqf. Youtube channels must also comply with the rules of the Youtube community guidelines. Keywords: Waqf, Youtube, Analysis, Sharia Economics